Disaster management in the Sundarbans delta ecosystem through environmental governance and sustainable planning - José Noronha Rodrigues; Sumanta Bhattacharya; Bhavneet Kaur Sachdev; Dora Cabete (Revista de Direito Econômico e Socioambiental)
The Sundarbans region is facing significant impacts on its ecosystem, business, agriculture, and environment due to inadequate disaster management. Storm surges, cyclones, and rising sea levels threaten the mangrove environment, causing permanent damage to farming and fishing communities, poverty, and revenue loss. The loss of mangroves affects ecological services like carbon sequestration, coastal protection, and biodiversity. To mitigate these risks, laws, growth promotion, catastrophe management plans, improved infrastructure, and public engagement in disaster response planning are necessary. Balancing environmental protection and economic expansion through climate-resilient farming techniques and sustainable agriculture is crucial. Tighter regulations, sustainable development strategies, stakeholder engagement, and advanced technology like AI can contribute to creating a resilient Sundarbans that protects the environment, improves community welfare, and ensures a sustainable future.